Exploring the association of infant receptive language and pitch variability in fathers' infant-directed speech. Issue 4 (26th April 2019) - QUIGLEY, Jean; NIXON, Elizabeth; LAWSON, Sarah
Abstract: The objective of this study was to examine the links between prosodic features of paternal Infant-Directed Speech (IDS) and child characteristics. Pitch variability measures were extracted from the speech samples of 50 fathers during unstructured play with their two-year-old children. Evidence for a link between child receptive language ability (measured by the Bayley Scales of Infant Development III) and fathers' pitch variability was obtained from Multiple Hierarchical Regression. Findings support the hypothesis that fathers tailor their speech to their children. This is one of the few studies to examine the relationship between fathers' IDS and child language ability.